Rediscovery of Liolaemus rabinoi (Iguania: Liolaemidae) after 35 years: redescription, biological and phylogenetic information, and conservation challenges - Abdala, Cristian Simón (2017)
Liolaemus is one of the most diverse genera of vertebrates, currently comprising 267 species classified into sev- eral monophyletic groups. Among them is the Liolaemus wiegmannii clade, including obligate sand-dwelling lizards with particular morphological traits and behavioural patterns associated with their habitat. One member of this group is Lio laemus rabinoi, a species from Argentina that has formerly been considered extinct. It was first found in 1972 on the mar- gins of the El Nihuil dam in San Rafael, Mendoza, Argentina. Four additional specimens of L. rabinoi were recorded in 1974–75, but subsequent searches were unsuccessful and resulted in the inclusion of this species in red conservation lists. In November 2010, new specimens of lizards assignable to L. rabinoi were found in an area of large sand dunes, 10 km from where it had been searched for in vain for years. We present a new diagnosis and redescription based on nine of these specimens (four males and five females) and provide biological, current distribution, and phylogenetic relationship data within the genus Liolaemus. We also analyse the particular human-induced effects on the environments where L. rabinoi occurs and discuss possible conservation measures to mitigate habitat loss